The Healthy Supermarket Coach: effects of a nutrition peer-education intervention in Dutch supermarkets on adolescents’ food purchases - Marlijn Huitink; Maartje P. Poelman; Jacob C. Seidell; Jos W. R. Twisk; S. Coosje Dijkstra (BMC Medicine)
Abstract Background Dutch adolescents predominantly purchase unhealthy snacks in supermarkets, which negatively influence their health. The aim of this study was to investigate the short- and longer-term effects of a nutrition peer-education intervention in supermarkets on food purchases and determinants of food purchase behaviour among adolescents of different education levels. Methods We performed a quasi-experimental study in three supermarkets (two intervention and one comparison school) in Amsterdam, the Netherlands. The intervention schools received a 45-min peer-education workshop in the supermarket near their school, and the comparison school received no intervention. The workshops also included a 2-week ‘healthy snacking challenge’ and were led by two young supermarket employees. Measurements were performed 2 weeks before the intervention (T0) 2 weeks after (T1) and 3 months (T2) after the intervention. Cash receipts were used to examine food purchases (n = 458) and questionnaires to examine determinants of food purchase behaviour (n = 463). Results The nutrition peer-education intervention did not improve food purchases but did improve several determinants of food purchase behaviour. Adolescents from the intervention schools reported improved nutritional knowledge (β = 0.38, 95% CI: 0.04–0.72) at T1, more favourable attitudes (β = 0.21, 95% CI: 0.00–0.42) and stronger social support (β = 0.27, 95% CI: 0.02–0.53) for healthy food purchases at T2 compared to those from the comparison schools. Adolescents with a low level of education reported more short- and longer-term improvements of determinants of food purchase behaviour compared to those with a higher level of education. Conclusions While nutrition peer education in supermarkets did not improve adolescents’ food purchases in the supermarket, determinants of food purchase behaviour did improve. The intervention was especially effective among adolescents with a low level of education. Nevertheless, to promote healthy food purchases of adolescents in supermarkets, more efforts are needed.